P.028 A milder congenital myopathy in the french canadians caused by a novel TNNT1 homozygous missense mutation. (5th June 2019) - Pellerin, D; Aykanat, A; Ellezam, B; Karamchandani, J; Mathieu, J; Chardon, J Warman; Konersman, CG; Beggs, AH; Brais, B; Chrestian, N
Abstract : Background: Mutations of the slow skeletal muscle troponin-T1 ( TNNT1 ) gene are a rare cause of nemaline myopathy. The phenotype is characterized by severe amyotrophy and contractures. Death from respiratory insufficiency occurs in infancy. We report on four French Canadians with a novel congenital TNNT1 -related myopathy.Methods: Patients underwent MRI of leg muscles, quadriceps biopsy and genetic testing. Wild type or mutated human TNNT1 mRNAs were co-injected with morpholinos in a zebrafish knockdown model to assess their relative abilities to rescue the morphant phenotype.Results: Three adults and one child shared a novel missense homozygous pathogenic variant in the TNNT1 gene. They developed from childhood slowly progressive limb-girdle weakness with spinal rigidity and contractures. They suffered from restrictive lung disease and recurrent episodes of infection-triggered rhabdomyolysis, which were relieved by dantrolene in one patient. Older patients remained ambulatory into their sixties. MRI of leg muscles showed symmetrical atrophy and fatty infiltration in a proximal-to-distal gradient. Biopsies showed multi-minicores, while nemaline rods were seen in half the patients. Wild type TNNT1 mRNA rescued the zebrafish morphants but mutant transcripts failed to rescue the morphants.Conclusions: This study expands the spectrum of TNNT1 -related myopathy to include a milder clinical phenotype caused by a functionally-confirmed novel missense mutation.